Iodine‐Catalysed Dissolution of Elemental Gold in Ethanol. (15th February 2022) - Zupanc, Anže; Heliövaara, Eeva; Moslova, Karina; Eronen, Aleksi; Kemell, Marianna; Podlipnik, Črtomir; Jereb, Marjan; Repo, Timo
Abstract: Gold is a scarce element in the Earth's crust but indispensable in modern electronic devices. New, sustainable methods of gold recycling are essential to meet the growing eco‐social demand of gold. Here, we describe a simple, inexpensive, and environmentally benign dissolution of gold under mild conditions. Gold dissolves quantitatively in ethanol using 2‐mercaptobenzimidazole as a ligand in the presence of a catalytic amount of iodine. Mechanistically, the dissolution of gold begins when I2 oxidizes Au 0 and forms a [Au I I2 ] − species, which undergoes subsequent ligand‐exchange reactions and forms a stable bis‐ligand Au I complex. H2 O2 oxidizes free iodide and regenerated I2 returns back to the catalytic cycle. Addition of a reductant to the reaction mixture precipitates gold quantitatively and partially regenerates the ligand. We anticipate our work will open a new pathway to more sustainable metal recycling with the utilization of just catalytic amounts of reagents and green solvents. Abstract : Gold can be dissolved in a sustainable manner with common household chemicals: iodine solution in ethanol, resembling diluted iodine tincture, green oxidant hydrogen peroxide and 2‐mercaptobenzimidazole, a compound used in medicinal applications. Catalytic reactions and green solvents are the basis for sustainable development and recycling of precious metals like gold.